EVALUATION OF COMMUNITY ASPIRATION EVENT (AJAMMA) THROUGH E-GOVERNMENT AS A PUBLIC SERVICE APPLICATION IN THE MAKASSAR CITY DPRD - Kasih, Andi Selvi Ratih; Nur, Andi Cudai; Sakawati, Herlina (Universitas Negeri Makassar, 2025)
This study aims to find out two things. The first is the evaluation result of the Community Aspirations Event (AJAMMA) through E-Government as a public service application at the Makassar City DPRD Secretariat. The two supporting and inhibiting factors are the AJAMMA application program in improving the quality of public services at the Makassar City DPRD Secretariat office. This study uses a qualitative approach. Data collection is done through observation techniques, interviews, and documentation. The data analysis technique used in this study was Spradley's data analysis through the stages of domain analysis, taxonomic analysis, compensatory analysis, and analysis of cultural themes. The results of this study indicate that the evaluation of the Community Aspirations Event (AJAMMA) through E-Government as a public service application at the Makassar City DPRD Secretariat based on the assessment of input indicators, process indicators, output indicators, and outcome indicators, can be stated to have gone well. This is supported by the convenience felt by the community in terms of channeling aspirations that have been present based on mobile applications. However, this mobile application-based service often experiences server disturbances which are affected by the user's internet connection.